2021
DOI: 10.5604/01.3001.0014.8324
|View full text |Cite
|
Sign up to set email alerts
|

Health expenditure in sub-Saharan Africa: Is it mean reversion? A Fourier unit root test approach

Abstract: The aim of the paper is to examine the mean reversion in health expenditure of 45 sub-Saharan African countries. The series on current health expenditure (percent of GDP in total), obtained from the World Development Indicators, each spanned the years 2000–2017. We employed the Fourier unit root test, which allows modelling structural breaks, to deal with any such breaks that could arise as a result of a small sample size (18 years) of data available on health expenditure of the selected countries. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…The unit root test [32] was carried out by the time series stationarity test method, and the test results showed that the index of the four dimensions of sports consumption intention and the lawn ecological benefit index sequence were all firstorder single-integer sequences, so the sports consumption intention index and the lawn ecological benefit index could be cointegration tested.…”
Section: Table 1 Unit Root Test Resultsmentioning
confidence: 99%
“…The unit root test [32] was carried out by the time series stationarity test method, and the test results showed that the index of the four dimensions of sports consumption intention and the lawn ecological benefit index sequence were all firstorder single-integer sequences, so the sports consumption intention index and the lawn ecological benefit index could be cointegration tested.…”
Section: Table 1 Unit Root Test Resultsmentioning
confidence: 99%